Crystallinity studies of PEKK and carbon fibre/PEKK composites: A review. (15th October 2021) - Pérez-Martín, Helena; Mackenzie, Paul; Baidak, Alex; Ó Brádaigh, Conchúr M.; Ray, Dipa
Abstract: Poly(etherketoneketone) (PEKK) is a thermoplastic, part of the poly(aryletherketone) (PAEK) family of polymers, with excellent mechanical performance and chemical resistance properties that make it an interesting candidate as a matrix for high-performance composites. Developing a thorough understanding of material properties is paramount in high-performance applications, and in the case of thermoplastics, crystallinity plays an essential role. This review paper covers the crystallisation morphology and structure of PEKK and CF/PEKK composites, crystallisation behaviour and kinetics under isothermal and dynamic conditions, and how these vary across different grades of PEKK with different terephthalic/isophthalic ratios. In the case of CF/PEKK composites, the impact of transcrystallinity development at the fibre-matrix interface, as well as the impact of carbon fibre inclusions on the crystallisation kinetics are discussed. Several crystallisation kinetics and transcrystallinity models available in literature are presented and discussed. The current limitations and future directions of CF/PEKK composites are also considered, covering manufacturing techniques such as autoclaving, automated tape placement, and 3D printing. This article draws comparisons to the better researched and established poly(etheretherketone) (PEEK) whenever relevant, in order to compliment the discussions on PEKK and CF/PEKK wherever literature is sparse. Highlights: Tuneability in PEKK impacts crystallisation capability and sets it apart from PEEK. Thermal history of PEKK and CF/PEKK plays an important role in its crystallinity. Transcrystallinity has been observed in some reinforced PEKK systems. Crystallisation kinetics of PEKK and CF/PEKK show a dual crystallisation mechanism. It is key to correlate lab-scale studies to industrial manufacturing scenarios.